Plasma levels of lecithin:cholesterol acyltransferase and risk of future coronary artery disease in apparently healthy men and women: a prospective case-control analysis nested in the EPIC-Norfolk population study - Holleboom, A. G. (The American Society for Biochemistry and Molecular Biology, 2010)
LCAT plays a key role in the maturation of HDL, as evidenced by low HDL-cholesterol levels in carriers of deleterious mutations in LCAT. However, the role of LCAT in atherosclerosis is unclear. We set out to study this in a prospective study. Plasma LCAT levels, which strongly correlate with LCAT activity, were measured in baseline nonfasting samples of 933 apparently healthy men and women who developed coronary artery disease (CAD) and 1,852 matched controls who remained free of CAD during 6 year follow-up. LCAT levels did not differ between cases and controls but were higher in women than men. Stratification into LCAT quartiles revealed a positive association with plasma LDL-cholesterol and triglyceride levels in the unexpected absence of an association with HDL-cholesterol. In mixed-gender analyses, the odds ratio (OR) for future CAD in the highest LCAT quartile versus the lowest was 1.00 [confidence interval (CI): 0.76–1.29, P for linearity = 0.902], although opposite trends were observed in men and women. In fact, high LCAT levels were associated with an increased CAD risk in women (unadjusted OR 1.45, CI: 0.94–2.22, P for linearity = 0.036). In contrast to our studies in carriers of LCAT mutations, the current data show that low LCAT plasma levels are not associated with increased atherosclerosis in the general population.